Variability in Leaf Canopy Architecture may be Related to Photosynthetic Efficiency and Carbon Fixation - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Karfakis, Theodore N. S. (International Journal of Bio-resource and Stress Management, 2023)
Leaves contribute greatly in plant growth and productivity for photosynthesis and nutrient contents. Thereexists a great diversity among plant species in growth form, leaf size and shape and canopy management. In addition, there exist some general relations across a wide range of species in leaf traits with respect to carbon fixation between species. The outer canopy leaves and its specific leaf area (SLA, leaf area per unit mass) tends to be correlated with leaf nitrogen per unit dry mass, photosynthesis and dark respiration sites (Wright et al., 2001). The availability of nutrients in leaves is essential for efficient plant function. Besides, a large variation among species with traits favours nutrient conservation. The importance of leaf nutrient content in plant function is well documented with respect to nutrient conservation, life span, high leaf mass per area, low nutrient concentration and low photosynthetic capacity (Reich et al., 1997)….